Ocorrência e aspectos etológicos de Porasilus barbiellinii Curran, 1934 (Diptera, Asilidae) predador da cigarrinha-das-pastagens Deois flavopicta (Stal, 1854) (Homoptera, Cercopidae) em pastagem de Brachiaria decumbens Stapf - Bueno, Vanda Helena Paes (1984)
This research deals with the study of biological and ethological aspects of Porasilus barbiellinii Curran, 1934 (Diptera, Asilidae), predator of the froghopper Deois flavopicta (Stal, 1854) (Homoptera, Cercopidae), in laboratory and in the field. The field experiment was set on a pasture of BAacktaAta dccumbcnò Stapf located in the municipal ity of Três Corações, State of Minas Gerais, Brazil. The following parameters were studied: morphological characteristics of egg, first instar larva and adult, egg period, egg viability, and population fluctuation of males and females. Mating behavior, oviposition, searching and predation activities in three five-day periods, during nine hours a day was also observed. Besides P. baAbtcZ Ztntt, other species of asilids collected in the field were: EtckcAax sp. , EtckcAax sp.?, AmvZyonyckuò sp. and Lccanta sp., however no competition was observed among the species. . HXáJ